Abundance, composition, and vertical transport of PAHs in marsh sediments - White, H. K.; Xu, L.; Lima, A. L.; Eglinton, T. I.; Reddy, C. M. (Environ Sci Technol, 2005)
Petroleum-derived hydrocarbons continue to persist in Wild Harbor, West Falmouth, MA, following a spill of No. 2 fuel oil in 1969 from the barge Florida. Recent analysis of marsh sediments revealed that residues of degraded oil are present with concentrations of total petroleum hydrocarbons as high as approximately 9 mg g(-1). Polycyclic aromatic hydrocarbons (PAHs) constitute only a minor fraction of these residues with maximum concentrations of 134 mirog g(-1), but their fate is of interest because of their potential toxicity to organisms. As compared to typical unweathered No. 2 fuel oil, the current distribution of PAHs in the sediments reflects substantial weathering by abiotic and biotic processes, specifically a preferential loss of naphthalenes relative to phenanthrenes, as well as isomer-specific biodegradation of alkylated PAHs. Based on comparison to results from an earlier study, it appears that little or no change has occurred to the distribution of PAHs since 1989, indicating that weathering at this site has stalled or is now proceeding at a significantly slower rate. To assess whether sediment-water partitioning and molecular diffusion in the interstitial medium are now the dominant processes controlling the vertical distribution of PAHs, downcore profiles were compared to a numerical model. While in some cases the model accurately reproduced the measured data, there were instances where the distribution of PAHs was slightly under or overestimated. Reasons for these discrepancies are discussed and are likely due to bioturbation, colloid-facilitated transport, or both. Assessment of the influence of these processes on the spilled oil expands our understanding of the overall fate of these compounds and their potential long-term effects on the environment.
White, Helen KXu, LiLima, Ana Lucia CEglinton, Timothy IReddy, Christopher MengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.2005/11/22 09:00Environ Sci Technol. 2005 Nov 1;39(21):8273-80.